ChemInform Abstract: Recent Applications of Aryltriazenes in Organic Synthesis via C—N/N—N Bond Cleavage. Issue 31 (August 2015) - Zhang, Yonghong; Cao, Dawei; Liu, Wenbo; Hu, Haiyan; Zhang, Xiaomei; Liu, Chenjiang
Abstract Review: 76 refs.